First record of a piebald leucistic smallspotted catshark Scyliorhinus canicula in a special area of conservation, UK - Neil D. Cook; Sarah L. Perry; Declan T. G. Quigley; Jo Cable; Sarah E. Perkins (Marine Biodiversity, 2025)
Colour aberrations are widely reported in vertebrates, but seldom for elasmobranchs. Shark trophic level varies ontogenetically and according to species, so atypical colouration may have implications for ecological fitness both as predator and prey. Here, we present, to our knowledge, the first and only record of a piebald leucistic smallspotted catshark Scyliorhinus canicula from Welsh waters, specifically in the Cardigan Bay Special Area of Conservation, UK. This adds to the five previous observations from the Irish and Mediterranean Seas. Sharks face numerous threats, including the physiological impacts of climate change. In this context, the prevalence and implications of leucism remain a knowledge gap.